The Construction of Prophetic Personae as Exemplars of Trust - Lyons, Michael A. 1967- (2024)
While the exemplary function of characters in ancient Israelite narrative texts has received significant attention, the construction of exemplars in prophetic texts has not. Here I examine the techniques by which the prophetic persona in the book of Isaiah was constructed as an exemplar of trust in YHWH, and I compare these techniques with similar ones in the books of Jeremiah, Micah, and Habakkuk. As I will show, passages describing the Isaian persona were taken up very quickly within the editorial history of the book and by subsequent authors in order to create further arguments about the importance of trust.